2000
DOI: 10.1046/j.1523-1755.2000.00017.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative mortality of hemodialysis and peritoneal dialysis in Canada

Abstract: The apparent survival advantage of peritoneal dialysis in Canada is due to lower comorbidity and a lower burden of acute onset end-stage renal disease at the inception of dialysis therapy. Hemodialysis and peritoneal dialysis, as practiced in Canada in the 1990s, are associated with similar overall survival rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
95
3
4

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(105 citation statements)
references
References 18 publications
(3 reference statements)
2
95
3
4
Order By: Relevance
“…We confirm earlier studies that found excess mortality among older patients, especially those with diabetes on PD (19,20). Our findings are based on the experience of a large and typical cohort of incident ESRD patients aged Ͼ65 in a large eastern state of the United States rather than of a single center with above-average experience with PD (2,15,22), or from populations with higher overall utilization of PD relative to HD than is seen in the United States that may not be representative of the way renal health care is delivered in this country (4,6,11,17,21). If replicated in other studies, these results may be relevant to the decision of patients nearing ESRD and their physicians in making decisions about which treatment to choose for long-term RRT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We confirm earlier studies that found excess mortality among older patients, especially those with diabetes on PD (19,20). Our findings are based on the experience of a large and typical cohort of incident ESRD patients aged Ͼ65 in a large eastern state of the United States rather than of a single center with above-average experience with PD (2,15,22), or from populations with higher overall utilization of PD relative to HD than is seen in the United States that may not be representative of the way renal health care is delivered in this country (4,6,11,17,21). If replicated in other studies, these results may be relevant to the decision of patients nearing ESRD and their physicians in making decisions about which treatment to choose for long-term RRT.…”
Section: Discussionmentioning
confidence: 99%
“…(1-22) These studies vary enormously with regard to population selection criteria, sample size, statistical methodology, definition of treatment, and availability of information on important potential confounders. The various results are conflicting: some studies have found a survival benefit for PD patients (12,16,18,20), others for those on HD (10,11,13), and still others have found mortality not to differ (2)(3)(4)(5)(6)(7)(8)14,15,19,21,22).Many of these previous studies, and all studies on US populations after 1983 have not adequately addressed a key methodologic issue: assessments that start at 4 or 6 mo after onset of RRT are likely to discard relevant events that occur between the first dialysis treatment and the chosen starting point of such studies, particularly modality switches and deaths. This omission can result in biased estimates of effect.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Five years survival rate for HD patients in Northern part of Iran was 23%, while in southern region of Iran was 46.8% (9,10). Various factors such as albumin and hemoglobin levels, adequacy of dialysis, dialysis duration, method of RRT, body mass index (BMI), etiology of kidney failure, comorbid diseases (i.e., diabetes mellitus, cardiovascular disease), and infection rates adversely affect the survival rates of HD patients (11)(12)(13)(14)(15)(16)(17). Among all the aforementioned factors, cardiovascular disease (CVD) is considered as a leading cause of morbidity and mortality among HD patients (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…By design, we studied hemodialysis patients without overt cardiac disease, and the generalizability of our findings to other populations with chronic kidney disease is not certain. Our results are applicable to approximately 50% of the dialysis population (18). The high dropout rate was anticipated because patients such as those in our study are usually referred for and then wait for renal transplantation.…”
Section: Discussionmentioning
confidence: 84%